2013
DOI: 10.1111/ggi.12114
|View full text |Cite
|
Sign up to set email alerts
|

Frailty among community‐dwelling elderly Mexican people: Prevalence and association with sociodemographic characteristics, health state and the use of health services

Abstract: The results suggest that older age, disability, comorbidity, cognitive impairment and depression could have an influence role in frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
96
3
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 36 publications
16
96
3
14
Order By: Relevance
“…Regarding marital status, the condition of having no mate, being single, widowed or divorced was also associated with frailty. Pre-frailty condition was associated with the absence of a mate in a study carried out with elderly residents of the urban area of Uberaba, Minas Gerais (18) , a similar result to the one found in the pre-frail and frail Mexican elderly (19) . It is known that the condition of frailty is multidimensional and such findings underline the need to better understand determination of social factors connected with frailty in the elderly.…”
Section: Discussionsupporting
confidence: 72%
“…Regarding marital status, the condition of having no mate, being single, widowed or divorced was also associated with frailty. Pre-frailty condition was associated with the absence of a mate in a study carried out with elderly residents of the urban area of Uberaba, Minas Gerais (18) , a similar result to the one found in the pre-frail and frail Mexican elderly (19) . It is known that the condition of frailty is multidimensional and such findings underline the need to better understand determination of social factors connected with frailty in the elderly.…”
Section: Discussionsupporting
confidence: 72%
“…In the literature, other studies have also detected an association between cognitive impairment and frailty, which were carried out at different contexts, such as: United States of America (22) ; Brazil (23) ; Canada (24) and Mexico (25) .…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[6][7][8][9][10] Studies conducted both in Brazil and in other countries have reported different prevalence rates, ranging from 6.9% to 40.6% among frail elderly individuals and 46.3% to 60.1% among prefrail individuals. 2,4,[11][12][13][14] In this regard, frailty syndrome should be targeted by earlier investigations and interventions, given its impact on elderly individuals, their families and society as a whole. 1 Despite recent initiatives, there are few Brazilian studies assessing this condition, and interventions that reduce the impact of this syndrome are still insufficient.…”
Section: Introductionmentioning
confidence: 99%